PERANCANGAN GAME DESAIN "RETURN OF THE AJI SAKA" SEBAGAI UPAYA PELESTARIAN AKSARA JAWA - Ganda Saputra, Kurniawan; Nurhadi Panindias, Asmoro (CITRAWIRA : Journal of Advertising and Visual Communication, 2020)
This design aims to make games not only for entertainment but also as a means of education, especially for the younger generation. Therefore, this design focuses on game design by incorporating historical elements such as Javanese script. Javanese script lessons have been taught to us since we were in elementary school, but unfortunately it is almost forgotten. In this modern era, information technology is not only used in the educational aspect, but also as entertainment in cyberspace. Many people like games which have several positive benefits and impacts, such as memory skills, practicing problem-solving skills, relieving stress, and increasing happiness. As in the process of designing the game "Return of the Aji Saka" is an approach tool for learning about culture, especially Javanese script. The inclusion of Javanese script into the design of this game can cause players to absorb cultural elements in it. In designing this game an initiative was taken to make all the characters in it like in the folklore "Legend of Javanese Script" so that it can make this game easier to understand as an educational game. This design method uses a sequential approach, in which a progress is seen as water flowing through the phases of planning, gathering the necessary requirements, identifying, conceptualizing, and designing. The results of this design can be in the form of promotional media such as artbooks, exhibition booths, online advertising as top line media (Above the line) and posters, X-banners, stickers, T-shirts, mugs, pins, key chains as lower line media (Below the line). The game design is expected to increase the younger generation's sense of concern for cultural preservation, especially Javanese script. In addition, it is hoped that it can become an alternative for teenagers to learn Javanese Script culture in the digital era like today.